LEGAL CONSEQUENCES OF OWNERSHIP OF UNREGISTERED LAND RIGHTS FROM THE PERSPECTIVE OF POSITIVE LAW - Noor, Muhammad Ferdian; Sukindar; Pasaribu, Benhard Kurniawan (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
The land registration process throughout Indonesia has not been fully completed, this phenomenon is influenced by the lack of public awareness in registering their land. Although the government has set a target to achieve comprehensive land registration through the Complete Systematic Land Registration Program (PTSL), the purpose of this study is to determine the legal consequences of not registering land rights in Indonesia and legal certainty in land registration. In this study, the method of accessing and researching takes a lot from library materials, namely materials containing new or up-to-date scientific knowledge, or new understandings of known facts or ideas, in this case including books, journals, dissertations or theses and other legal materials. The legal consequences of not registering land rights in Indonesia in the form of certificates can have significant implications for legal certainty and protection of landowner rights. Land registration is an important step to ensure legal certainty, where land title certificates serve as strong evidence of ownership. Without registration, landowners are at risk of legal uncertainty, which can result in land disputes and difficulties in conducting other legal transactions. The results of the implementation and execution of electronic land registration as referred to in paragraph (1) are in the form of data, electronic information, and/or electronic documents. That in the process of implementing land registration with Government Regulation Number 24 of 1997 concerning Land Registration states that land registration is a series of activities carried out by the Government continuously, sustainably and regularly.